2000
DOI: 10.1007/s004240000309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ammonia on sodium absorption in rat proximal colon

Abstract: The influence of ammonia on sodium and chloride fluxes in rat proximal colon was studied in Ussing chamber experiments. Under short-circuit conditions, the proximal colon absorbed sodium and secreted chloride. The presence of ammonia (30 mmol 1(-1) mucosal) diminished Na+ absorption, but had hardly any influence on Cl- fluxes. Blocking the apical Na+/H+ exchanger isoform NHE2 by amiloride or HOE642 diminished absorptive Na+ and Cl- fluxes. In contrast, the NHE3-specific antagonist S3226 was ineffective. Amilor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…However, the extent to which K ϩ secretion may have contributed to the measured current was unclear. In contrast, Cermak et al (6) found little effect of luminal NH 4 ϩ on Cl Ϫ flux in rat colon. It is unlikely that an apical K ϩ conductance is a contributing factor in this study, (15).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…However, the extent to which K ϩ secretion may have contributed to the measured current was unclear. In contrast, Cermak et al (6) found little effect of luminal NH 4 ϩ on Cl Ϫ flux in rat colon. It is unlikely that an apical K ϩ conductance is a contributing factor in this study, (15).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies in rat and human colon as well as in cultured epithelial cell lines have demonstrated that NH 4 ϩ can inhibit Na ϩ absorption (6, 7) as well as Cl Ϫ secretion (6,16,31,32,37,48). The T84 secretory colonic cell line was used to show that basolateral NH 4 ϩ can affect cAMP-and cGMPdependent Cl Ϫ secretion but not carbachol-induced Ca 2ϩ -dependent secretion (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even more, our results indicate that while NHE1 and NHE4 would have a housekeeping role in steady state pH i NHE2 would be mainly involved in Na + uptake. In fact, NHE2 has shown to be a major pathway for NaCl absorption in rat proximal colon [34] and to participate in Na + absorption in mouse colonic crypts [35]. Additionally, the capacity of T84 cells for absorbing Na + has been reported and informed as HOE-694 sensitive, indicating the participation of the Na + /H + exchanger [19].…”
Section: Discussionmentioning
confidence: 99%